the Perbedaan Kekerasan Permukaan Resin Komposit Setelah Paparan Asap Rokok Filter dan Rokok Elektrik - Alvi Rizqi Amaliyah; Arwin Diva Nafida; Berta Ivana Priladiantika; Bambang Tri Hartomo (Denta Journal Kedokteran Gigi, 2022)
Background: Composite resin is a dental filling material that has several mechanical properties, one of which is surface hardness. Surface hardness can increase due to several factors such as smoking habits. Filter cigarette is the second most common type of cigarette in Indonesia and electric cigaretteis the third most common type of cigarette in Indonesia. Both types of cigarettes can affect the surface hardness of the composite resin due to a decrease in the pH of saliva produced from cigarette smoke. Objective: This study aimed to determine the difference in surface hardness of thecomposite resin after exposure to filter cigarette smoke and electric cigarette. Methods: 27 samples of nanohybrid composite resin were divided into three groups. Group 1 as a control group was immersed in artificial saliva and was not exposed to cigarette smoke, group 2 wasthe group that was treated with filter cigarette smoke and group 3 was the group that was treated with electric cigarette. Furthermore, the groups were tested for surface hardness using a Vickers hardness tester. Results: The surface hardness test of the composite resin showed an increase in the control group and a decrease in the treatment group, with the highest decrease in the filter cigarette smoke treatment group. The results of the paired t-test and one-way ANOVA test showed that the p-value was >0.00 so there was no difference between the pre-test and post-test mean differences in each group and there was no difference between the mean of each group Conclusion: There was no difference before and after exposure to filter cigarette or electric cigarette smoke.